2021
DOI: 10.1007/s11187-021-00545-x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and state dependence in firms’ access to bank credit

Abstract: This paper investigates firms’ access to bank credit in eleven euro area countries over the periods 2014–2019. Exploiting firm-level longitudinal data, we analyse loan demand and credit rationing probabilities, accounting for sample selection, unobserved heterogeneity and state dependence. Empirical results show that small and informationally opaque businesses, with deteriorated public support and credit history, face greater difficulties in obtaining bank loans. Furthermore, we provide evidence of a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 78 publications
1
6
0
Order By: Relevance
“…Analysing the impact of prior financing difficulties, we find that those firms that were denied credit or discouraged from applying before the pandemic are about 11.5% more likely to face credit rejection and 10.4% less likely to apply for additional credit during the COVID-19 crisis. Coherently with Pigini et al ( 2016 ) and Aristei & Angori ( 2022 ), our results highlight that financing difficulties tend to persist over time, due to observed firm characteristics, unobserved heterogeneity, and true state dependence. We also provide evidence of a significant discouragement effect of prior credit restrictions on firms’ loan demand behaviour during the pandemic, in line with the findings of Cowling et al ( 2022a ).…”
Section: Empirical Analysissupporting
confidence: 87%
See 1 more Smart Citation
“…Analysing the impact of prior financing difficulties, we find that those firms that were denied credit or discouraged from applying before the pandemic are about 11.5% more likely to face credit rejection and 10.4% less likely to apply for additional credit during the COVID-19 crisis. Coherently with Pigini et al ( 2016 ) and Aristei & Angori ( 2022 ), our results highlight that financing difficulties tend to persist over time, due to observed firm characteristics, unobserved heterogeneity, and true state dependence. We also provide evidence of a significant discouragement effect of prior credit restrictions on firms’ loan demand behaviour during the pandemic, in line with the findings of Cowling et al ( 2022a ).…”
Section: Empirical Analysissupporting
confidence: 87%
“…As discussed in the extant literature (Fernandez, 2022 ; Wellalage & Kumar, 2021 ; Xing et al, 2020 ), the endogeneity of green management may be due to the fact that firms’ environmental behaviour and financing policies may be jointly determined by unobservable factors related to firm quality, attitudes towards risk, and creditworthiness. At the same time, previous studies (Aristei & Angori, 2022 ; Pigini et al, 2016 ) have shown that credit demand and financing constraints tend to persist over time due to persistence in observed and unobserved heterogeneity and to true state dependence, highlighting the necessity of accounting for the endogeneity of pre-pandemic financing conditions. Moreover, Cowling et al ( 2022a ) recently show that firms that have been credit rejected in the pre-pandemic period have a lower loan demand during the COVID-19 crisis and that enterprises scarred by previous rejection are significantly less likely to be granted credit during the pandemic.…”
Section: Empirical Analysismentioning
confidence: 96%
“…This pattern is confirmed in our sample of SMEs. 14 The high persistence in firms’ demand for bank financing is motivated by the limited recourse to capital markets and by the role of application costs (Aristei & Angori, 2022 ). The development of sustainable and diversified financing for micro firms other than banks is also important to support small and young firms’ growth.…”
Section: Discussionmentioning
confidence: 99%
“…Large companies are subject to disclosure requirements and balance sheet controls that facilitate the bank assessment of their capital strength and related loan riskiness. In contrast, SMEs tend to have less complete accounts, which makes the information asymmetry between potential borrowers and lenders more severe, resulting in less reliance on bank debt (Aristei & Angori, 2022; Deloof et al., 2019; Myers, 1984; Myers & Majluf, 1984).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Large companies are subject to disclosure requirements and balance sheet controls that facilitate the bank assessment of their capital strength and related loan riskiness. In contrast, SMEs tend to have less complete accounts, which makes the information asymmetry between potential borrowers and lenders more severe, resulting in less reliance on bank debt (Aristei & Angori, 2022;Deloof et al, 2019;Myers, 1984;Myers & Majluf, 1984). 3 Moreover, starting with the seminal paper of Cressy (1996), a relevant part of the literature has empirically investigated the role of bank credit relative to both SMEs and start-ups' survival (Astebro & Bernhardt, 2003;Carter & Van Auken, 2006;Castaldo et al, 2020;Cole & Sokolyk, 2018;Cosh et al, 2009;Crepon & Duguet, 2003;Deloof & Vanacker, 2018;Wamba et al, 2017).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%